Tinker Bell and the lost treasure - Huston, Anjelica; Liu, Lucy, 1968-; McCartney, Jesse, 1987-; Raven, 1985-; Chenoweth, Kristin; Whitman, Mae, 1988-; Walt Disney Studios Home Entertainment (Firm); Walt Disney Pictures ([United States] : Walt Disney Studios Home Entertainment, 2009)
Tinker Bell and her fairy friends are trying to change summer into fall and get ready for the big fall celebration, and learn about the magic of true friendship along the way.
Title from container.
Widescreen.
With the voices of Anjelica Huston, Lucy Liu, Jesse Mccartney, Raven Symone, Kristin Chenoweth, Mae Whitman.
MPAA rating: G.
DVD; Dolby Digital 5.1 Surround Sound.
English, French or Spanish dialogue; English, French or Spanish subtitles; English subtitled for the deaf and hard of hearing (SDH).
Keywords: Tinker Bell (Fictitious character) -- Juvenile drama; Fairies -- Juvenile drama; Magic -- Juvenile drama; Friendship -- Juvenile drama; Moonstones -- Juvenile drama; Animated films; Children's films; Feature films; Films for the hearing impaired